Analysis of the needs and possibilities of using psychological help among the society - Gorecka, Adrianna; Wieteska, Małgorzata; Osial, Natalia; Maj, Dominik; Gorecka, Dagmara (Journal of Education, Health and Sport, 2022)
Introduction Young people find themselves in stressful situations more and more frequently. Mental health and access to professional psychical help is necessary. Unfortunately, the availability of the psychologist's offices, as well as knowledge about mental health, is very limited. Aim of the study We aimed to check factors that cause stress and the access to psychological help in Poland. Material and method In order to analyze the issue, an Internet survey was prepared and disseminated in February and March 2022. Results Over 80% of respondents claimed that sometime in their life they needed psychological help, although the majority of them did not seek professional help. 41,1% of people who took part in the survey could get help from psychologists in their place of work or study, but over 83% of them did not seek help there. Everyday problems and situations in work, school or university were mentioned as the most stressful situations (63,7%). According to the respondents' opinion, problems with concentration and nervousness (80,6% and 76,6% respectively) due to stress have a negative influence on their health. 74,2% of young people consider themselves as not stress-resistant. The best option to deal with stress is to listen to music or to converse with their closest ones. Conclusion Everyone should have ensured good access to psychological help. There is a great demand for it, regardless of gender or age. Despite the need to see an expert, the majority of people do not ask for help.